Effects of aided smoking cessation counselling with exhaled carbon monoxide measurement versus conventional counselling on smokers’ intention to quit and cigarette consumption - Noorsyarida Shadan,; Hizlinda Tohid,; Tan, Chai-Eng; Nuraida Baharuddin,; Noor Azimah Muhammad,; Shamsul Azhar Shah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Feedback on exhaled carbon monoxide (CO) levels may potentially improve smokers’ motivation to quit. However, evidence to support its use is still lacking. This study aimed to examine how providing feedback on exhaled CO measurement affected smokers’ intention to quit and cigarette consumption short term. This non-randomised controlled trial was conducted at a government health clinic. The control group (n=132) received conventional counselling using the 5A approach and pamphlets, whereas the intervention group (n=132) received similar counselling along with feedback on exhaled CO measurements. Subjects’ intention to quit in the next month and current cigarette consumption were assessed at baseline and again four weeks post-counselling. At the baseline, there were significant differences between the groups in terms of gender (p=0.002), ethnicity (p=0.004), marital status (p=0.002), age of smoking initiation (p<0.001), nicotine dependence (p=0.001) and quit intention (p<0.001). Compared to the control group, those who received intervention started smoking at a younger age and had greater nicotine dependence, but they had stronger quit intentions. One month post-counselling, there were no differences in quit intention (p=0.389) and cigarette consumption (p=0.902) between the groups. However, within-group analysis shows both a significant improvement in quit intention (p<0.001 for both groups) and a reduction in cigarette consumption (p<0.001 for both groups) after the counselling. None of the participants quit smoking at follow-up. In conclusion, both conventional smoking cessation counselling and counselling with feedback on exhaled carbon monoxide levels were similarly effective in improving smokers’ quit intention and reducing cigarette consumption. However, this enhanced motivation was inadequate to make them quit.